Estudo comparativo de intervenções voltadas à promoção de atividade física em idosos sedentários no lazer - Valerio, Mirella Pinto [UNIFESP] (2012)
Brazil has shown an increasingly older demographic profile. There are more than 13 million people over 65 years old (10.2% of the Brazilian population) in the country nowadays. Even though physical activities contribute to older adults’ autonomy and independence, their level of sedentarianism is still high. Taking into account the complexity regarding the commitment to physical activities, this study aimed at analyzing the effects of two different interventions whose intention was to change the sedentary behavior of older adults in their free time. The variable result was the change in the average of minutes used for physical activities in their free time, per week. Therefore, a quasi-experimental study was carried out with members of a cohort of older adults who live in an urban area (a project called EPIDOSO) and who have been classified as sedentary regarding their leisure activities, according to the International Physical Activity Questionnaire (IPAQ), i. e., they had not even spent ten minutes/week doing these activities. The sample comprised 121 older adults, divided in three groups: class (CG), stimulus (SG) and control ones. Groups CG and SG underwent two different interventions for three months. Members of CG took part in two 60-minute classes per week with aerobic activities and flexibility, balance and muscle strengthening exercises. Older adults in the SG got a folder with questions about the benefits of carrying out physical activities, besides information on how to practice them; follow-up involved phone calls during this period. Evaluation was performed by re-applying the IPAQ at the end of the interventions (T90) and three months after that (T180). The control group was reevaluated after 180 days (T180). Variance analysis of repeated measures (T90 and T180) with a categorical factor of three levels (Class, Stimulus and Control) showed that, at the end of the interventions (T90 days), the older adults in CG had significantly increased their weekly average of physical activities by comparison with the ones in the SG (111.1 min/week and 42.7 min/week, respectively). However, the evaluation that was performed three weeks after the end of the interventions (T180) showed that the average of both groups was similar (71.5 min/week and 71.8 min/week) and superior to the one collected in the control group (43.3 min/week). Therefore, I have concluded that strategies which comprise classes or handing out folders with guidelines about physical activities, followed by phone calls, have similar effects. Both contribute to decrease in sedentarianism levels of older adults’ free time by comparison with the control group.